2013
DOI: 10.1002/hep.26442
|View full text |Cite
|
Sign up to set email alerts
|

α-fetoprotein levels after interferon therapy and risk of hepatocarcinogenesis in chronic hepatitis C

Abstract: Post-IFN treatment ALT and AFP levels are significantly associated with hepatocarcinogenesis. Measurement of these values is useful for predicting future HCC risk after IFN treatment. Suppression of these values after IFN therapy reduces HCC risk even in patients without HCV eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
264
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(281 citation statements)
references
References 44 publications
14
264
3
Order By: Relevance
“…Previous studies have reported that advanced fibrosis, advanced age, lower albumin levels, lower platelet counts, and higher α‐fetoprotein (AFP) levels before and after treatment are important predictors of HCC in patients who achieve SVR with interferon‐based treatment 14, 15, 16. However, the risk factors for the development of HCC in patients who achieve SVR after DAA treatment have not been adequately clarified in a prospective study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that advanced fibrosis, advanced age, lower albumin levels, lower platelet counts, and higher α‐fetoprotein (AFP) levels before and after treatment are important predictors of HCC in patients who achieve SVR with interferon‐based treatment 14, 15, 16. However, the risk factors for the development of HCC in patients who achieve SVR after DAA treatment have not been adequately clarified in a prospective study.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Therefore, future studies are needed to determine whether our results are in agreement with long-term, large cohort studies that include various population subgroups. Nevertheless, we believe that our results have important clinical implications for clinicians considering an individual patient's HCC surveillance and/or treatment strategy.…”
mentioning
confidence: 58%
“…Nevertheless, SVR patients remain at risk of HCC development, especially those with old age, high baseline gamma-glutamyltransferase levels, advanced liver fibrosis or comorbidity such as diabetes [206][207][208]. High APRI 6 months after the end of treatment [209] and high posttreatment ALT or AFP levels [210] were independent factors significantly associated with HCC development. These data indicate that regular monitoring for HCC screening and good control of comorbidities after achieving a SVR are mandatory for HCV patients.…”
Section: Laboratory Testing After Hcv Curementioning
confidence: 99%
“…These data indicate that regular monitoring for HCC screening and good control of comorbidities after achieving a SVR are mandatory for HCV patients. Older age, male gender, advanced fibrosis, severe steatosis, lower serum albumin levels, non-SVR, and higher post-interferon-treatment ALT or AFP levels are identified as independent factors significantly associated with HCC development [210]. Occurrence of HCC is not a rare event during and after antiviral treatment in older HCV patients [211] or HCV patients with advanced fibrosis [210].…”
Section: Laboratory Testing After Hcv Curementioning
confidence: 99%
See 1 more Smart Citation